Cardiac troponin I antibodies induce cardiomyocyte damage and alter cell morphology - Furkel, Jennifer; Zirkenbach, Vanessa A.; Knoll, Maximilian; Öttl, Renate; Rein, Katrin; Abdollahi, Amir; Frey, Norbert; Konstandin, Mathias; Kaya, Ziya (International journal of molecular sciences, 2025)
Circulating heart-reactive autoantibodies (aAbs) detected in a variety of heart diseases (e.g., myocarditis, dilated cardiomyopathy, and myocardial infarction) have been associated with the progression of heart failure and a poor prognosis. However, the underlying mechanisms remain largely unknown. We investigated the effects of murine plasma containing aAbs against cardiac troponin I (cTnI) on neonatal rat cardiomyocytes (NRCMs). An autoimmune response to cTnI in A/J mice was induced, and anti-cTnI-aAbs were quantified. After 21 days, cardiac function, inflammation, fibrosis, and apoptosis were evaluated. In complementary in vitro liquid biopsy experiments, NRCMs were incubated with murine plasma containing high anti-cTnI-aAb levels or corresponding controls. Morphological phenotyping was performed using the C-MORE fluorescent image-based analysis workflow. Immunization with cTnI resulted in high anti-cTnI-aAb production, followed by myocardial inflammation, fibrosis, and impaired ejection fraction. NRCMs exposed to anti-cTnI-aAb-containing plasma showed reduced cell size, altered shape and radius, and elevated rate of dead cells in cell cycle analysis (p < 0.01, for 20% plasma). Together, these findings suggest a direct interaction of anti-cTnI-aAbs on cardiomyocytes, likely promoting adverse myocardial remodeling in vivo.